Pengujian Efisiensi Pasar Setengah Kuat Secara Informasi terhadap Pengumuman Inisiasi Dividen - Ronowati Tjandra (Journal of Accounting and Investment, 2006)
This research explore the examination of  semistrong form-informationally efficient capital market  in Jakarta Stock Exchange towards the initiation dividend announcements. This examination focused on the effort to show the influence of initiation dividend announcement towards abnormal return at the event date and the around of that announcement and the speed of adjustment of stock price to the equilibrium price. This research using 17 firms which was identified announcing  initiation dividend 1 year after IPO (Initial Public Offering)  as samples during the period 2000  until 2003 after be selected according to the conditional that stated in this research. This research was an event study that take 10 days before and 10 days after the date of announcement, so that the estimation period which be used in this examination were 21 days. The result of this research shows  that capital market of Indonesia, which represented by Jakarta Stock Exchange have already informationally- semistrong form efficient market to the initiation dividend announcement. This result was indicated by the information content in the initiation dividend announcement that  positive and significant about 6% in the event date, and surely, there was speed of adjustment from the market reaction to initiation dividend announcement that take 1 day only i.e.one day at the event date. This research also supported the agency cost model and the signaling theory, which shown by both the  high level of agency cost and informational asymmetry.